2016
DOI: 10.21606/drs.2016.344
|View full text |Cite
|
Sign up to set email alerts
|

What a designer can change: a proposal for a categorisation of artefact-related aspects

Abstract: This paper proposes a categorisation of artefact-related aspects that in different ways set people's preconditions for acting with technology. The categorisation can serve as a starting point for discussing which aspects are relevant to consider from a Design for Sustainable Behaviour perspective. The categorisation sorts these aspects into different layers: from the over-arching layer of enabled activity, through artefact type(s), operative functions, interactive functions, and finally communicative functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The application in this paper is to understand how design to encourage more circular behaviour at an individual level can help as part of a wider system transition. Although crucially, as noted by Selvefors et al [38], it is not possible to design behaviour, it is only possible to design the preconditions which define how somebody may behave. Meaning that behaviour change alone is not a reliable enough method as the only route to system change.…”
Section: Design For Behaviour Changementioning
confidence: 99%
“…The application in this paper is to understand how design to encourage more circular behaviour at an individual level can help as part of a wider system transition. Although crucially, as noted by Selvefors et al [38], it is not possible to design behaviour, it is only possible to design the preconditions which define how somebody may behave. Meaning that behaviour change alone is not a reliable enough method as the only route to system change.…”
Section: Design For Behaviour Changementioning
confidence: 99%
“…Third, the paper considers the characteristics in relation to their level of generality in regards to the design of an appliance by structuring the characteristics according to the layers of design proposed by Selvefors et al (2016). While others commonly discuss one characteristic separately (see for example McCalley and Midden, 1998;McCalley et al, 2011) or several characteristics independently of each other (Thornander et al, 2011) the findings in this paper highlight the need to address the different characteristics in relation to each other as they interact to create preconditions for use.…”
Section: Contribution Of the Findingsmentioning
confidence: 89%
“…A procedure for analysing interview data described by Miles and Huberman (1994) was followed in which data segments were clustered into themes and subsequently grouped in subthemes. A categorisation of artefact-related aspects proposed by Selvefors et al (2016) was used as a basis for organising the identified design characteristics according to five hierarchically ordered layers: communicative functions, interactive functions, operative functions, artefact type(s), and the overall layer enabled activity. This particular categorisation was used as it hierarchically arranges artefact-related aspects into different layers of design that influence people's preconditions for interacting with technology in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the user makes the decision to separate materials for recycling, take products to a recycling center, or notably, not putting it in general waste containers [17]. Nevertheless, it is not possible to design behavior; it is only possible to the influence people's ability to act with artifacts by designing for behavior [75].…”
Section: Design Measuresmentioning
confidence: 99%